Pengaruh Pemberdayaan dan Motivasi Kerja Terhadap kinerja Karyawan Pada Astra Motor Honda Cabang Ubud Di Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Intense competition in the business sector drives every company to enhance employee performance to stay competitive and grow. Astra Motor Honda Ubud Branch in Gianyar also encountered issues with employee performance, including problems related to empowerment and work motivation. The purpose of this study is to assess how empowerment and work motivation impact employee performance. This research is quantitative in nature and was carried out at the Astra Motor Honda Ubud Branch in Gianyar, involving a population of 38 employees. This study employs a saturated sampling method, ensuring that every member of the population is included as a research subject. Data collection was conducted through the use of a questionnaire. Hypothesis testing was performed via multiple linear regression analysis. The findings of the analysis lead to the following conclusions: 1) empowerment has a positive and significant impact on employee performance, 2) work motivation has a positive and significant impact on employee performance, and 3) both empowerment and work motivation collectively have a positive and significant impact on employee performance.